Effect of amino-, mercapto-silane coupling as a molecular bridge of polyvinyl chloride ion-selective membrane on silicon nitride for nitrate ISFET sensors - Chaisriratanakul, Woraphan; Bunjongpru, Win; Pankiew, Apirak; Srisuwan, Awirut; Jeamsaksiri, Wutthinan; Chaowicharat, Ekalak; Thornyanadacha, Nutthaphat; Pengpad, Putapon; Phromyothin, Darinee (My University, 2020)
This paper presents a modification of a Si3N4 Polyvinyl chloride (PVC) membrane on a surface of an ion selective field effect transistor (ISFET) using silane with two different functional groups for comparison of nitrate sensing characteristics. Effects of amino (NH2) and thiol groups (SH) toward structures and characteristics of nitrate sensors were analyzed using the following techniques: ellipsometry, scanning electron microscope (SEM), infrared spectroscopy (FTIR), zeta potential and electrochemical impedance spectroscopy (EIS). After surface modification, the thickness of the silane layers for both cases were similar with uniform surface topology. Absolute zeta potentials of PVC ion-selective membrane (7.65 mV) and Si3N4 surface modification with MPTMS (-51.46 mV) reflected the surface functional group and showed that membranes could be bonded to the PVC ion-selective membrane. Since APTMS produced higher EIS than MPTMS, the resulting nitrate sensors modified by MPTMS had higher sensitivity than the sensors with APTMS. Finally, the modified sensors had a useful life time of 3 months.